2008
DOI: 10.1007/s10725-008-9277-4
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of salicylic acid and silicon on oxidative damage and antioxidant activity in spinach (Spinacia oleracea L. cv. Matador) grown under boron toxicity and salinity

Abstract: We investigated individual and combined effects of salinity, soil boron (B), silicon (Si) and salicylic acid (SA) on the activities of major antioxidant enzymes (superoxide dismutase, SOD; catalase, CAT and ascorbate peroxidase, APX) and nonenzymatic antioxidants (AA), proline, chlorophyll, anthocyanin, H 2 O 2 concentration, stomatal resistance (SR), lipid peroxidation (MDA), membrane permeability (MP), and the uptake of sodium (Na), chloride (Cl), boron and Si of spinach plants. In general, salinity signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
58
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(73 citation statements)
references
References 54 publications
11
58
2
2
Order By: Relevance
“…Additionally, we observed that Si can regulate wound-related stress to plants by increasing the activities of antioxidant enzymes and decreasing the level of lipid peroxidation compared to non-Sitreated plants. These results further strengthen the role of Si as an efficient treatment for the improvement of plant resistance to abiotic stresses, as noted in earlier studies (Eraslan et al 2008;Li et al 2005). To improve crop yields, our results support the application of Si to control the negative effects of wounding stress to crop plants.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, we observed that Si can regulate wound-related stress to plants by increasing the activities of antioxidant enzymes and decreasing the level of lipid peroxidation compared to non-Sitreated plants. These results further strengthen the role of Si as an efficient treatment for the improvement of plant resistance to abiotic stresses, as noted in earlier studies (Eraslan et al 2008;Li et al 2005). To improve crop yields, our results support the application of Si to control the negative effects of wounding stress to crop plants.…”
Section: Discussionsupporting
confidence: 89%
“…Similar results related to the reduction of the ascorbate pool were obtained from cotton (Parida and Das 2005), Cassia angustifolia (Agarwal and Pandey 2004), Critimum maritimum (Ben Hamed et al 2007), spinach (Eraslan et al 2008) and naked oat (Xu et al 2008) under salt conditions. Some studies indicated that under salt stress, the ascorbate pool in cucumber plants (Parida and Das 2005) and non-enzymatic antioxidants in explants of apple (Molassiotis et al 2006) increased.…”
Section: Discussionsupporting
confidence: 80%
“…Under osmotic stress conditions, plants, in addition to producing antioxidants, also accumulate in the cytosol compatible solutes such as proline that originally were thought to function as osmotic buffers. Proline acts as a mediator of osmotic adjustment, protector of macromolecules such as proteins and membranes, sink for energy, scavenger of free radicals and also as a stress-related signal (Ashraf and Foolad 2007;Eraslan et al 2008;Rahnama and Ebrahimzadeh 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Application of silicon has been reported to be able to control diseases (Rodrigues et al 2003) and pests (Ranganathan et al 2006), alleviate toxicity of some heavy metals (Shi et al 2010), and relieve boron stress (Gunes et al 2007b) and salt stress (Gong et al 2006;Liang et al 2006). Silicon addition markedly reduced MDA concentration in stressed plant species (Liang 1999;Gunes et al 2007c;Eraslan et al 2008). To the best of our knowledge, there is no previous report on micropropagation of C. wilsonii.…”
Section: Introductionmentioning
confidence: 95%